Studying red cell distribution width in Iraqi persons with type 2 diabetes mellitus in Najaf City: a case-control study - Maysam Riyadh Mohammed Hussein Alaasam; Karrar Mohammed Abbas Al-buthabhak; Ahmed Mech; Shamim Riadh Mohammed Hussein (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Red cell distribution width (RDW) is a parameter measured routinely in standard blood cell counts, reflecting the variability in red cell size and volume. Numerous studies have identified a significant correlation between RDW and various health disorders, including cardiovascular diseases, malignancies, obesity, and chronic kidney diseases. Purpose: to study red cell distribution width in Iraqi persons with type 2 diabetes and assess its role in providing clinical information about glycemic control. Materials and methods. This case-control study included 300 participants, 150 Iraqi persons with type 2 diabetes (77 female and 73 male) in Najaf City, and 150 healthy controls (79 female and 71 male). Age, weight, systolic blood pressure, diastolic blood pressure, complete blood count, glycated hemoglobin (HbA1c), and C-reactive protein levels were assessed. In patients with diabetes, disease duration, medications, and complications were recorded. People with a history of anemia, renal failure, heart disease, hypertension, thyroid disorder, pregnancy, and conditions leading to chronic inflammation, such as rheumatoid arthritis, diabetic neuropathy, diabetic retinopathy, and diabetic nephropathy, were excluded from the study. Results. RDW was significantly higher in people with diabetes (14.77 ± 3.56) than in healthy controls (12.19 ± 1.10), p < 0.0001. In the diabetes group, no statistically significant correlation was noted between RDW and disease duration (p = 0.143). RDW was strongly and directly associated with HbA1c and C-reactive protein levels (p < 0.0001 and р = 0.002, respectively). Conclusions. RDW was higher in people with type 2 diabetes than in healthy controls. RDW levels are affected by glycemic control because a higher HbA1c level is associated with a higher RDW. Thus, RDW can be considered a marker of glycemic control in clinical practice.